Preparation method and application of Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement

By optimizing the composition and preparation process of Mo-Re alloys, combined with additive manufacturing and thermal isostatic pressing processes, the insufficient performance of existing hydrogen-resistant embrittlement materials in high temperature, high tensile stress and hydrogen-rich environments has been solved, and Mo is realized -High-efficient hydrogen embrittlement resistance of Re alloy in hydrogen smelting nozzle applications.

CN118957378BActive Publication Date: 2025-02-25江西国创院新材料有限公司 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411132846.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-02-25
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

The existing hydrogen embrittlement-resistant materials are difficult to meet the application needs of hydrogen smelting nozzles in high temperature, high tensile stress and hydrogen-rich environments, mainly due to the hydrogen trap provided by the phase interface between the diffuse particles and the matrix and the introduced second phase particles to hydrogen embrittlement. The impact of failure.

Method used

Mo-Re single-phase solid solution alloy is adopted to reduce the solid solubility of H in Mo-Re alloy by optimizing the alloy composition and preparation process. Combined with additive manufacturing and thermal isostatic pressing, a high structural strength and toughness are prepared. Mo-Re alloy.

Benefits of technology

The excellent strength, ductility and hydrogen embrittlement resistance of Mo-Re alloys at high temperatures are achieved, which effectively reduces the hydrogen diffusion coefficient, avoids the hydrogen enrichment problem caused by secondary particles, and meets the performance requirements of hydrogen smelting nozzles.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a preparation method and application of a hydrogen embrittlement-resistant Mo-Re single-phase solid solution alloy, belonging to the field of advanced non-ferrous metal materials. The hydrogen embrittlement-resistant Mo-Re alloy provided by this invention comprises, by mass percentage, 67-92% Mo, 5-30% Re, and 0.5-3% M, where M is a combination of W, Ta, and Nb, or one or more of these elements. The preparation method involves using clean, dry Mo, Re, and M element powders as raw materials, performing laser additive manufacturing with appropriate parameters, and then combining this with hot isostatic pressing to obtain a Mo-Re sample. The resulting product has a single-phase solid solution microstructure, achieving high structural strength and toughness while reducing the solid solubility of hydrogen in the Mo-Re alloy, thus enabling the alloy to possess excellent resistance to hydrogen embrittlement. This invention features a rationally designed material structure and a simple, controllable preparation method, facilitating large-scale industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a preparation method and application of a Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement, belonging to the field of advanced nonferrous metal materials. Background Art

[0002] As a major carbon emitter, the steel industry accounts for about 15% of my country's total carbon emissions. Under the background of the "dual carbon" goal, how to embark on the road of "green steel" is an urgent problem that the entire industry needs to solve. Hydrogen metallurgy technology uses hydrogen as a reducing agent instead of carbon reduction, which is an important way to reduce CO2 emissions from long-process steelmaking and ensure the green and sustainable development of the steel industry. At present, strategic plans for hydrogen smelting have been proposed in the metallurgical fields at home and abroad, including ULCOS in Europe, HYBRT in Sweden, COURSE50 project in Japan, and Zhongjin Mining in my country. As the core component of hydrogen metallurgy, the nozzle needs to work for a long time under high temperature, high tensile stress and hydrogen-rich environment. In a hydrogen-rich environment, hydrogen atoms will be adsorbed and diffused into the metal, and will gather at the phase interface, grain boundary, dislocation and pores, microcracks and other locations, reducing the strength of the metal lattice, accelerating the movement of local dislocations, promoting the formation of vacancies and nanopores, significantly deteriorating the performance of the nozzle material and causing it to fracture brittlely, so strict requirements are placed on the high-temperature mechanical properties and hydrogen embrittlement resistance of the nozzle material.

[0003] At present, the materials used to resist hydrogen embrittlement mainly include nickel-based high-temperature alloys, high-entropy alloys, steels, and high-strength and plastic aluminum alloys. The main method is to introduce dispersed second-phase particles to adsorb hydrogen atoms and inhibit hydrogen diffusion to improve the material's resistance to hydrogen embrittlement. However, hydrogen smelting nozzles face harsh working conditions such as high temperature (>800°C), high tensile stress, and hydrogen-rich atmosphere. Existing hydrogen embrittlement-resistant materials are difficult to meet their application requirements, which is mainly attributed to two points. On the one hand, the interface between the dispersed particles and the matrix will provide more reversible and irreversible hydrogen traps. In a high-temperature hydrogen-rich atmosphere, hydrogen atoms will be enriched at the interface between the dispersed particles and the matrix, thus becoming a crack source for hydrogen embrittlement failure. On the other hand, although the introduced second-phase particles will increase the high-temperature strength of the material, the enrichment of hydrogen atoms will significantly deteriorate the plasticity of the material, leading to rapid failure of the material. Existing hydrogen embrittlement-resistant materials are difficult to meet the application requirements of hydrogen smelting nozzles. Summary of the invention

[0004] In view of the urgent need for hydrogen embrittlement resistance of nozzle materials for hydrogen metallurgy, the present invention provides a hydrogen embrittlement resistant Mo-Re single-phase solid solution alloy and a preparation method thereof, which can achieve high structural strength and toughness while reducing the solid solubility of H in the Mo-Re alloy, so that the alloy can have good hydrogen embrittlement resistance.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A hydrogen embrittlement resistant Mo-Re single-phase solid solution alloy is composed of the following elements by mass percentage: 67-92% of Mo, 5-30% of Re and 0.5-3% of M element, wherein the M element is a single element or a combination of multiple elements such as W, Ta and Nb.

[0007] Furthermore, the Re content in the alloy is preferably 10-25%, and further preferably 13-23%.

[0008] Furthermore, the alloy is a single-phase solid solution with a density of >99.95% and a grain size of about 5 to 30 microns.

[0009] Furthermore, the room temperature tensile strength of the alloy is 700~1100 MPa and the elongation is 15~30%.

[0010] The present invention provides a method for preparing a hydrogen embrittlement resistant Mo-Re alloy, which is characterized by comprising the following steps:

[0011] Step 1: According to the designed alloy component mass percentage, spherical Mo powder with a particle size of 40-80 microns, Re powder with a particle size of 40-80 microns, W powder with a particle size of 40-80 microns, Ta powder with a particle size of 40-80 microns and Nb powder with a particle size of 40-80 microns are used as raw materials, or spherical MoReWTaNb alloy powder with a particle size of 40-80 microns prepared according to the alloy component mass percentage is used; the powder is pre-mixed by a three-dimensional mixer at a speed of 30r / min and a mixing time of 5h to obtain a standby mixed powder; the mixed powder is placed in a vacuum drying oven and kept warm at 60°C for 10h;

[0012] Step 2: After rinsing the substrate, ultrasonic cleaning is performed with anhydrous ethanol and formaldehyde for 30 minutes respectively to remove impurities and oil stains on the surface of the substrate; after drying, a spare substrate is obtained;

[0013] Step 3: The obtained mixed powder is loaded into the powder cylinder, the power is turned on to heat the spare substrate, and the laser powder deposition process based on nozzle automatic powder feeding is adopted to adjust the preparation process to obtain the Mo-Re initial sample, wherein the laser power is 800~1500 W, the scanning speed is 300~600 mm / min, the powder feeding rate is 8~30 g / min, and the substrate heating temperature is 200~500℃;

[0014] Step 4: The initial Mo-Re sample is placed in a hot isostatic pressing furnace for treatment. The process is as follows: first, the temperature is raised to 1400~1600 ℃ at a heating rate of ≤20℃ / min, the pressure in the furnace is 80~150 MPa, the insulation time is 1~5 h, and then it is cooled to room temperature at a rate of 10℃ / min to obtain the final sample.

[0015] Furthermore, in the step 1, the powder particle size is preferably 40-70%, and more preferably 50-60%.

[0016] Furthermore, in step three, the laser power is preferably 1000-1200 W, and the scanning speed is preferably 400-500 mm / min.

[0017] Furthermore, in step 4, the holding time is preferably 2 to 4 h, the scanning speed is preferably 400 to 500 mm / min, and the holding time is further preferably 3 to 4 h.

[0018] Furthermore, the present invention provides an application method of the aforementioned alloy, which is used to manufacture a hydrogen smelting nozzle.

[0019] The Mo-Re single-phase solid solution alloy for hydrogen embrittlement resistance in hydrogen smelting proposed by the present invention utilizes the advantages of excellent strength, ductility, creep resistance and low hydrogen diffusion coefficient of Mo-Re alloy at high temperature to effectively ensure the strength and plasticity of the nozzle in the high temperature environment of hydrogen smelting.

[0020] The molybdenum content in the alloy of the present invention is not less than 67%. The hydrogen diffusion coefficient of molybdenum in the hydrogen metallurgical process temperature range of 600-1000°C is several orders of magnitude lower than that of other hydrogen embrittlement resistant metals such as iron, nickel, and aluminum. As the matrix of the alloy, the diffusion of hydrogen into the alloy at high temperature of hydrogen metallurgy is greatly reduced, and the intrinsic hydrogen diffusion coefficient of the alloy is reduced to the greatest extent.

[0021] The present invention aims to solve the problem of hydrogen enrichment caused by dispersed particles and leading to hydrogen embrittlement failure. By optimizing alloy composition, regulating laser power and hot isostatic pressing process, a Mo-Re single-phase solid solution alloy is prepared, thereby avoiding the problem of hydrogen enrichment caused by secondary particles from the root.

[0022] In the aspect of optimizing alloy composition, the present invention uses rhenium as the element with the second highest content, and together with molybdenum, it constitutes the main element of the alloy. Rhenium and molybdenum have similar physical and chemical properties and atomic structures. The two can form a single-phase solid solution alloy with a body-centered cubic structure within a certain composition range. Due to the existence of the "rhenium effect", the molybdenum-rhenium alloy overcomes the room temperature and low temperature brittleness of tungsten, and has high melting point, high strength, high plasticity, low plastic brittle transition temperature and more excellent high temperature mechanical properties. More importantly, the present invention uses rhenium as the main added element, which can effectively improve the hydrogen dissolution energy of the molybdenum-based alloy. With the increase of rhenium content, the hydrogen dissolution energy of the alloy is further improved, making it difficult for hydrogen to enter the face-centered cubic alloy, thereby reducing the concentration of hydrogen in the alloy, which is conducive to inhibiting hydrogen embrittlement and meeting the performance requirements of hydrogen metallurgical nozzles. It can effectively maintain the single-phase body-centered cubic structure of the alloy and the phase stability after multi-element alloying, ensuring that the alloy has good hydrogen resistance and hydrogen resistance while maintaining a single-phase structure. In addition, in order to inhibit the formation of brittle hydrides in the alloy, the present invention adds alloying elements tungsten, tantalum and niobium (content is about 0.5-3%) to reduce the hydride formation enthalpy of the multi-component alloy at high temperature, making it difficult for brittle hydrides to form in the alloy, thereby further improving the high-temperature hydrogen embrittlement resistance of the alloy.

[0023] In terms of regulating laser power and hot isostatic pressing process, the present invention adopts a larger laser power to promote alloy solid solution and densification. In addition, the unique rapid cooling process of additive manufacturing technology will induce more obvious lattice distortion, thereby increasing the hydrogen migration barrier and further reducing the hydrogen diffusion coefficient of the alloy. The use of a larger sintering pressure and temperature in hot isostatic pressing can further promote the densification of elements inside the alloy, promote the solid solution and composition homogenization between multiple elements inside the alloy, and improve the tensile strength, elongation and hydrogen embrittlement resistance of the alloy. In short, through the coordinated optimization of alloy composition design and preparation process, a Mo-Re alloy material with excellent high-temperature mechanical properties and good hydrogen embrittlement resistance and a near-net forming preparation method adapted thereto are developed, which are particularly suitable for hydrogen smelting nozzles.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention provides a new Mo-Re alloy for resisting hydrogen embrittlement, which is particularly suitable for hydrogen smelting nozzles.

[0026] (2) Through the coordinated optimization of alloy composition design and preparation process, a Mo-Re alloy material with excellent high-temperature mechanical properties and good resistance to hydrogen embrittlement was obtained.

[0027] (3) Through the preparation method of "additive manufacturing + hot isostatic pressing", the near-net forming of Mo-Re alloy with integrated structure and function is achieved, and the nozzle product can be directly obtained. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0029] A high temperature hydrogen embrittlement resistant single-phase Mo-Re alloy for hydrogen metallurgy, the composition of which is 80-82% Mo, 17-19% Re, 1.8-2.0% Ta and 1-1.2% W in terms of mass percentage;

[0030] The preparation method comprises the following steps:

[0031] Step 1: Weigh the powder according to the designed ratio, and pre-mix the powder through a three-dimensional mixer at a speed of 30 r / min and a mixing time of 5 h to obtain a mixed powder for use; place the mixed powder in a vacuum drying oven and keep it warm at 60° C. for 10 h;

[0032] Step 2: After rinsing the substrate, ultrasonic cleaning is performed with anhydrous ethanol and formaldehyde for 30 minutes respectively to remove impurities and oil stains on the surface of the substrate; after drying, a spare substrate is obtained;

[0033] Step 3: The obtained mixed powder is loaded into the powder cylinder, the power is turned on to heat the spare substrate, and the laser powder deposition process based on nozzle automatic powder feeding is adopted to adjust the preparation process to obtain the Mo-Re sample, wherein the laser power is 1000 W, the scanning speed is 400 mm / min, the powder feeding rate is 10 g / min, and the substrate heating temperature is 400°C;

[0034] Step 4: The Mo-Re sample is placed in a hot isostatic pressing furnace for treatment. The process is as follows: first, the temperature is raised to 1400 °C at a heating rate of 10 °C / min, the pressure in the furnace is 100 MPa, the insulation time is 2 h, and then it is cooled to room temperature at a rate of 10 °C / min to obtain the final sample.

[0035] The sample grain size is about 15 microns, the structure is a single-phase solid solution, and no secondary precipitation phase and intermetallic compound phase are found. The tensile properties of the Mo-Re alloy in Example 1 are tested, and the room temperature tensile strength is 850MPa, and the elongation after fracture is 20.4%. The tensile strength at 800℃ is 420MPa, and the elongation after fracture is 17.5%;

[0036] The Mo-Re alloy of Example 1 was subjected to high-temperature gas-phase hydrogen charging and then to high-temperature mechanical testing. After hydrogen charging, the tensile strength of the sample at 800°C was 390 MPa, and the elongation after fracture was 12.5%. Example 2

[0037] A high temperature hydrogen embrittlement resistant single-phase Mo-Re alloy for hydrogen metallurgy, the composition of which is 74-76% Mo, 21-23% Re and 2.8-3.0% Nb in terms of mass percentage;

[0038] The preparation method comprises the following steps:

[0039] Step 1: Weigh the powder according to the designed ratio, and pre-mix the powder through a three-dimensional mixer at a speed of 30 r / min and a mixing time of 5 h to obtain a mixed powder for use; place the mixed powder in a vacuum drying oven and keep it warm at 60° C. for 10 h;

[0040] Step 2: After rinsing the substrate, ultrasonic cleaning is performed with anhydrous ethanol and formaldehyde for 30 minutes respectively to remove impurities and oil stains on the surface of the substrate; after drying, a spare substrate is obtained;

[0041] Step 3: The obtained mixed powder is loaded into the powder cylinder, the power is turned on to heat the spare substrate, and the laser powder deposition process based on nozzle automatic powder feeding is adopted to adjust the preparation process to obtain the Mo-Re sample, wherein the laser power is 1200 W, the scanning speed is 500 mm / min, the powder feeding rate is 15 g / min, and the substrate heating temperature is 450°C;

[0042] Step 4: The Mo-Re sample is placed in a hot isostatic pressing furnace for treatment. The process is as follows: first, the temperature is raised to 1500 °C at a heating rate of 10 °C / min, the pressure in the furnace is 150 MPa, the insulation time is 3 h, and then it is cooled to room temperature at a rate of 10 °C / min to obtain the final sample.

[0043] The sample grain size is about 10 microns, the structure is a single-phase solid solution, and no secondary precipitation phase and intermetallic compound phase are found. The tensile properties of the Mo-Re alloy in Example 2 are tested, and the room temperature tensile strength is 980MPa, and the elongation after fracture is 25.7%. The tensile strength at 800℃ is 501MPa, and the elongation after fracture is 20.1%;

[0044] The Mo-Re alloy of Example 2 was subjected to high-temperature gas phase hydrogen charging and then to high-temperature mechanical testing. After hydrogen charging, the tensile strength of the sample at 800°C was 445 MPa, and the elongation after fracture was 15.4%. Example 3

[0045] A high temperature hydrogen embrittlement resistant single-phase Mo-Re alloy for hydrogen metallurgy, the composition of which is 84-86% Mo, 11-13% Re, 0.8-1.2% Ta and 1.8-2.2% Nb in terms of mass percentage;

[0046] The preparation method comprises the following steps:

[0047] Step 1: Weigh the powder according to the designed ratio, and pre-mix the powder through a three-dimensional mixer at a speed of 30 r / min and a mixing time of 5 h to obtain a mixed powder for use; place the mixed powder in a vacuum drying oven and keep it warm at 60° C. for 10 h;

[0048] Step 2: After rinsing the substrate, ultrasonic cleaning is performed with anhydrous ethanol and formaldehyde for 30 minutes respectively to remove impurities and oil stains on the surface of the substrate; after drying, a spare substrate is obtained;

[0049] Step 3: The obtained mixed powder is loaded into the powder cylinder, the power is turned on to heat the spare substrate, and the laser powder deposition process based on nozzle automatic powder feeding is adopted to adjust the preparation process to obtain the Mo-Re sample, wherein the laser power is 1300 W, the scanning speed is 540 mm / min, the powder feeding rate is 20 g / min, and the substrate heating temperature is 450°C;

[0050] Step 4: The Mo-Re sample is placed in a hot isostatic pressing furnace for treatment. The process is as follows: first, the temperature is raised to 1550 °C at a heating rate of 10 °C / min, the pressure in the furnace is 120 MPa, the insulation time is 5 h, and then it is cooled to room temperature at a rate of 10 °C / min to obtain the final sample.

[0051] The sample grain size is about 27 microns, the structure is a single-phase solid solution, and no secondary precipitation phase and intermetallic compound phase are found. The tensile properties of the Mo-Re alloy in Example 3 were tested, and the room temperature tensile strength was 760 MPa, and the elongation after fracture was 16.5%. The tensile strength at 800°C was 390 MPa, and the elongation after fracture was 15.1%;

[0052] The Mo-Re alloys of Example 3 were subjected to high-temperature gas-phase hydrogen charging and then to high-temperature mechanical tests. After hydrogen charging, the tensile strength of the samples at 800°C was 300 MPa, and the elongation after fracture was 10.2%. Example 4

[0053] A high temperature hydrogen embrittlement resistant single-phase Mo-Re alloy for hydrogen metallurgy, the composition of which is 79-81% Mo, 16-18% Re, 0.8-1.2% Ta, 0.8-1.2% W and 0.8-1.2% Nb in terms of mass percentage;

[0054] The preparation method comprises the following steps:

[0055] Step 1: Weigh the powder according to the designed ratio, and pre-mix the powder through a three-dimensional mixer at a speed of 30 r / min and a mixing time of 5 h to obtain a mixed powder for use; place the mixed powder in a vacuum drying oven and keep it warm at 60° C. for 10 h;

[0056] Step 2: After rinsing the substrate, ultrasonic cleaning is performed with anhydrous ethanol and formaldehyde for 30 minutes respectively to remove impurities and oil stains on the surface of the substrate; after drying, a spare substrate is obtained;

[0057] Step 3: The obtained mixed powder is loaded into the powder cylinder, the power is turned on to heat the spare substrate, and the laser powder deposition process based on nozzle automatic powder feeding is adopted to adjust the preparation process to obtain the Mo-Re sample, wherein the laser power is 1200 W, the scanning speed is 600 mm / min, the powder feeding rate is 23 g / min, and the substrate heating temperature is 470°C;

[0058] Step 4: The Mo-Re sample is placed in a hot isostatic pressing furnace for treatment. The process is as follows: first, the temperature is raised to 1600 °C at a heating rate of 10 °C / min, the pressure in the furnace is 180 MPa, the insulation time is 3 h, and then it is cooled to room temperature at a rate of 10 °C / min to obtain the final sample.

[0059] The sample grain size is about 13 microns, the structure is a single-phase solid solution, and no secondary precipitation phase and intermetallic compound phase are found. The tensile properties of the Mo-Re alloy in Example 4 were tested, and the room temperature tensile strength was 870 MPa, and the elongation after fracture was 22.7%. The tensile strength at 800°C was 460 MPa, and the elongation after fracture was 19.1%;

[0060] The Mo-Re alloys of Example 4 were subjected to high-temperature gas-phase hydrogen charging and then to high-temperature mechanical tests. After hydrogen charging, the tensile strength of the samples at 800° C. was 420 MPa, and the elongation after fracture was 14.6%.

[0061] Comparative Example 1

[0062] A high-temperature hydrogen embrittlement-resistant single-phase Mo-Re alloy for hydrogen metallurgy, the composition of which is 93-95% Mo, 3-4% Re, 1.8-2.0% Ta and 1-1.2% W by mass percentage.

[0063] The preparation method comprises the following steps:

[0064] Step 1: Weigh the powder according to the designed ratio, and pre-mix the powder through a three-dimensional mixer at a speed of 30 r / min and a mixing time of 5 h to obtain a mixed powder for use; place the mixed powder in a vacuum drying oven and keep it warm at 60° C. for 10 h;

[0065] Step 2: After rinsing the substrate, ultrasonic cleaning is performed with anhydrous ethanol and formaldehyde for 30 minutes respectively to remove impurities and oil stains on the surface of the substrate; after drying, a spare substrate is obtained;

[0066] Step 3: The obtained mixed powder is loaded into the powder cylinder, the power is turned on to heat the spare substrate, and the laser powder deposition process based on nozzle automatic powder feeding is adopted to adjust the preparation process to obtain the Mo-Re sample, wherein the laser power is 1000 W, the scanning speed is 400 mm / min, the powder feeding rate is 10 g / min, and the substrate heating temperature is 400°C;

[0067] Step 4: The Mo-Re sample is placed in a hot isostatic pressing furnace for treatment. The process is as follows: first, the temperature is raised to 1400 °C at a heating rate of 10 °C / min, the pressure in the furnace is 100 MPa, the insulation time is 2 h, and then it is cooled to room temperature at a rate of 10 °C / min to obtain the final sample.

[0068] Due to the low Re content, the toughening effect of Re on the Mo matrix is ​​not obvious. The grain size of the sample is about 45 microns. The structure is still a single-phase solid solution, but cracks appear inside the alloy. No secondary precipitation phase and intermetallic compound phase are found. The tensile properties of the Mo-Re alloy in Comparative Example 1 are tested. The room temperature tensile strength is 340 MPa, and the elongation after fracture is 8%. The tensile strength at 800℃ is 102 MPa, and the elongation after fracture is 3%.

[0069] The Mo-Re alloy of comparative example 1 was subjected to high-temperature gas phase hydrogen charging and then to high-temperature mechanical testing. After hydrogen charging, the tensile strength of the sample at 800°C was 80 MPa, indicating brittle fracture.

[0070] Comparative Example 2

[0071] A high-temperature hydrogen embrittlement-resistant single-phase Mo-Re alloy for hydrogen metallurgy, the composition of which is 42-44% Mo, 49-51% Re, 0.8-1.2% W and 1.8-2.2% Nb in terms of mass percentage.

[0072] The preparation method comprises the following steps:

[0073] Step 1: Weigh the powder according to the designed ratio, and pre-mix the powder through a three-dimensional mixer at a speed of 30 r / min and a mixing time of 5 h to obtain a mixed powder for use; place the mixed powder in a vacuum drying oven and keep it warm at 60° C. for 10 h;

[0074] Step 2: After rinsing the substrate, ultrasonic cleaning is performed with anhydrous ethanol and formaldehyde for 30 minutes respectively to remove impurities and oil stains on the surface of the substrate; after drying, a spare substrate is obtained;

[0075] Step 3: The obtained mixed powder is loaded into the powder cylinder, the power is turned on to heat the spare substrate, and the laser powder deposition process based on nozzle automatic powder feeding is adopted to adjust the preparation process to obtain the Mo-Re sample, wherein the laser power is 1200 W, the scanning speed is 500 mm / min, the powder feeding rate is 15 g / min, and the substrate heating temperature is 450°C;

[0076] Step 4: The Mo-Re sample is placed in a hot isostatic pressing furnace for treatment. The process is as follows: first, the temperature is raised to 1500 °C at a heating rate of 10 °C / min, the pressure in the furnace is 150 MPa, the insulation time is 3 h, and then it is cooled to room temperature at a rate of 10 °C / min to obtain the final sample.

[0077] Due to the high Re content in the alloy, the grain size of the sample is significantly refined to about 6 microns, and the Mo-Re intermetallic compound phase appears in the structure, which will significantly deteriorate the alloy performance. The tensile properties of the Mo-Re alloy in Comparative Example 2 were tested, and the room temperature tensile strength was 560 MPa, the elongation after fracture was 11.4%, and the tensile strength at 800℃ was 204 MPa, and the elongation after fracture was 6.0%.

[0078] The two Mo-Re alloys of the comparative example were subjected to high-temperature gas phase hydrogen charging and then to high-temperature mechanical tests. After hydrogen charging, the tensile strength of the samples at 800°C was 103 MPa, and the elongation after fracture was brittle fracture.

[0079] Comparative Example 3

[0080] A high-temperature hydrogen embrittlement-resistant single-phase Mo-Re alloy for hydrogen metallurgy, the composition of which is 84-86% Mo and 14-16% Re in percentage by mass.

[0081] The preparation method comprises the following steps:

[0082] Step 1: Weigh the powder according to the designed ratio, and pre-mix the powder through a three-dimensional mixer at a speed of 30 r / min and a mixing time of 5 h to obtain a mixed powder for use; place the mixed powder in a vacuum drying oven and keep it warm at 60° C. for 10 h;

[0083] Step 2: After rinsing the substrate, ultrasonic cleaning is performed with anhydrous ethanol and formaldehyde for 30 minutes respectively to remove impurities and oil stains on the surface of the substrate; after drying, a spare substrate is obtained;

[0084] Step 3: The obtained mixed powder is loaded into the powder cylinder, the power is turned on to heat the spare substrate, and the laser powder deposition process based on nozzle automatic powder feeding is adopted to adjust the preparation process to obtain the Mo-Re sample, wherein the laser power is 1200 W, the scanning speed is 600 mm / min, the powder feeding rate is 23 g / min, and the substrate heating temperature is 470°C;

[0085] Step 4: The Mo-Re sample is placed in a hot isostatic pressing furnace for treatment. The process is as follows: first, the temperature is raised to 1600 °C at a heating rate of 10 °C / min, the pressure in the furnace is 180 MPa, the insulation time is 3 h, and then it is cooled to room temperature at a rate of 10 °C / min to obtain the final sample.

[0086] Since no trace alloying elements (W, Ta, and Nb) were added, the grain size of the sample was about 35 microns, the structure was still a single-phase solid solution, and no secondary precipitation phase and intermetallic compound phase were found. The tensile properties of the Mo-Re alloy in Comparative Example 4 were tested, and the room temperature tensile strength was 610 MPa, and the elongation after fracture was 14.3%. The tensile strength at 800°C was 370 MPa, and the elongation after fracture was 7.8%.

[0087] The three Mo-Re alloys of the comparative example were subjected to high-temperature gas-phase hydrogen charging and then to high-temperature mechanical tests. After hydrogen charging, the tensile strength of the samples at 800°C was 210 MPa, and the elongation after fracture was 3.1%.

[0088] Comparative Example 4

[0089] A high-temperature hydrogen embrittlement-resistant single-phase Mo-Re alloy for hydrogen metallurgy comprises the following components by mass percentage: 79-81% Mo, 16-18% Re, 0.8-1.2% Ta, 0.8-1.2% W and 0.8-1.2% Nb.

[0090] The preparation method comprises the following steps:

[0091] Step 1: Weigh the powder according to the designed ratio, and pre-mix the powder through a three-dimensional mixer at a speed of 30 r / min and a mixing time of 5 h to obtain a mixed powder for use; place the mixed powder in a vacuum drying oven and keep it warm at 60° C. for 10 h;

[0092] Step 2: After rinsing the substrate, ultrasonic cleaning is performed with anhydrous ethanol and formaldehyde for 30 minutes respectively to remove impurities and oil stains on the surface of the substrate; after drying, a spare substrate is obtained;

[0093] Step 3: The obtained mixed powder is loaded into the powder cylinder, the power is turned on to heat the spare substrate, and the laser powder deposition process based on nozzle automatic powder feeding is adopted to adjust the preparation process to obtain the Mo-Re sample, wherein the laser power is 1200 W, the scanning speed is 800 mm / min, the powder feeding rate is 35 g / min, and the substrate heating temperature is 470°C;

[0094] Step 4: The Mo-Re sample is placed in a hot isostatic pressing furnace for treatment. The process is as follows: first, the temperature is raised to 1300 °C at a heating rate of 10 °C / min, the pressure in the furnace is 50 MPa, the insulation time is 3 h, and then it is cooled to room temperature at a rate of 10 °C / min to obtain the final sample.

[0095] Due to the excessive scanning speed and powder feeding rate, and the low hot isostatic pressing temperature and pressure, the density of the obtained sample is poor, the grain size of the sample is about 16 microns, and the structure is a single-phase solid solution. The tensile properties of the Mo-Re alloy in Comparative Example 4 were tested, and the room temperature tensile strength was 400 MPa, and the elongation after fracture was 6%. Its tensile strength at 800℃ was 180 MPa, and the elongation after fracture was brittle fracture.

[0096] The Mo-Re alloy in Comparative Example 4 was subjected to high-temperature gas-phase hydrogen charging and then to high-temperature mechanical tests. After hydrogen charging, the tensile strength of the sample at 800°C was 60 MPa, and the elongation after fracture was brittle fracture.

Claims

1. A Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement, characterized in that: The alloy is composed of the following elements by mass percentage: 67-92% of Mo, 5-30% of Re and 0.5-3% of M element, wherein the M element is a single element or a combination of multiple elements selected from W, Ta and Nb. The alloy is prepared by the following steps: Step 1: according to the mass percentage of the alloy components, spherical Mo powder with a particle size of 40-80 microns, Re powder with a particle size of 40-80 microns, W powder with a particle size of 40-80 microns, Ta powder with a particle size of 40-80 microns and Nb powder with a particle size of 40-80 microns are used as raw materials, or spherical MoReWTaNb alloy powder with a particle size of 40-80 microns prepared according to the mass percentage of the alloy components is used; the powder is pre-mixed by a three-dimensional mixer at a speed of 30r / min and a mixing time of 2-15h to obtain a mixed powder for standby; the mixed powder is placed in a vacuum drying oven and kept warm at 60°C for 10h; Step 2: After rinsing the substrate, ultrasonic cleaning is performed with anhydrous ethanol and formaldehyde for 30 minutes respectively to remove impurities and oil stains on the surface of the substrate; after drying, a spare substrate is obtained; Step 3: The obtained mixed powder is loaded into a powder cylinder, the power is turned on to heat the standby substrate, and the initial Mo-Re sample is obtained by laser powder deposition based on nozzle automatic powder feeding, wherein the laser power is 800~1500 W, the scanning speed is 300~600mm / min, the powder feeding rate is 8~30 g / min, and the substrate heating temperature is 200~500℃; Step 4: The initial Mo-Re sample is placed in a hot isostatic pressing furnace for treatment. The process is as follows: first, the temperature is raised to 1400~1600 ℃ at a heating rate of ≤20℃ / min, the pressure in the furnace is 80~150 MPa, the insulation time is 1~5 h, and then it is cooled to room temperature at a rate of 10℃ / min to obtain the final sample.

2. The hydrogen embrittlement resistant Mo-Re single-phase solid solution alloy according to claim 1, characterized in that: The Re content in the alloy is 10~25%.

3. The Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement according to claim 1, characterized in that: The Re content in the alloy is 13~23%.

4. The Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement according to claim 1, characterized in that: The alloy is a single-phase solid solution with a density of >99.95% and a grain size of 5~30 microns.

5. The Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement according to claim 1, characterized in that: The room temperature tensile strength of the alloy is 700~1100 MPa and the elongation is 15~30%.

6. The Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement according to claim 1, characterized in that: The powder particle size in step 1 is 40-70 microns.

7. The Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement according to claim 1, characterized in that: The powder particle size in step 1 is 50-60 microns.

8. The Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement according to claim 1, characterized in that: In step 3, the laser power is 1000~1200 W and the scanning speed is 400~500 mm / min.

9. The Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement according to claim 1, characterized in that: The insulation time in step 4 is 2 to 4 h.

10. The Mo-Re single-phase solid solution alloy resistant to hydrogen embrittlement according to claim 1, characterized in that: The insulation time in step 4 is 3 to 4 hours.

11. The application method of the hydrogen embrittlement resistant Mo-Re single-phase solid solution alloy according to any one of claims 1 to 10, characterized in that: The alloy is used to make hydrogen smelting nozzles.

Citation Information

Patent Citations

  • Extrusion preparation method of molybdenum-rhenium alloy pipe

    CN111036893A

  • A molybdenum alloy target material, its preparation method and application

    CN114934260A

  • Composite target disc containing columnar crystal grain structure as well as preparation method and application of composite target disc

    CN118231206A